Motor flexibility to stabilize the toe position during obstacle crossing in older adults: an investigation using an uncontrolled manifold analysis - Suda, Yuki; Kodama, Kentaro; Nakamura, Takahito; Sakazaki, Juntaro; Higuchi, Takahiro (Frontiers in Sports and Active Living, 2024)
An age-related decrease in the ability to exploit the abundant degrees of freedom of the body, referred to as motor flexibility, leads to a heightened fall risk. The present study investigated motor flexibility to stabilize the toe position during obstacle crossing in older adults and its correlation with the magnitude of foot elevation. Twenty-six older adults (70.9 ± 7.4 years old) and 21 younger adults (25.4 ± 5.0 years old) walked and crossed an obstacle, during which the dominant limb was always the leading limb. An uncontrolled manifold (UCM) analysis was used to quantify the flexibility during obstacle crossing as the synergy index, with the vertical toe position being regarded as the performance variable and the segment angles of the lower limbs as the elemental variables. The results showed that older participants had a significantly lower synergy index for the trailing limb before the moment of obstacle crossing than younger participants, suggesting reduced flexibility in part. The results also showed that, regardless of age, foot elevation was negatively correlated with the synergy index, suggesting that a so-called "conservative strategy" (i.e., a tendency to show extraordinarily high foot elevation to ensure collision avoidance) may be related to their reduced motor flexibility.